Classifier-approximator modular neural network for accurate estimation of dynamic system parameters - Materka, Andrzej (Zielona Góra: Uniwersytet Zielonogórski)
Principles of employing feedforward artificial neural networks for fast and robust estimation of dynamic system parameters are reviewed briefly. In this approach, the neural network approximates the mapping from the system observation space into the parameter space. It is pointed out that for the conventional neural network architectures the network size and time needed for its training increase quickly with the estimated parameter range and with the approximation accuracy level required.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka